Assessment of highly concentrated pear juice production through single-run forward osmosis using sodium lactate as the draw solute. (November 2022) - Li, Zihe; Xiao, Shengjian; Xiong, Qinmei; Wu, Chongde; Huang, Jun; Zhou, Rongqing; Jin, Yao
Abstract: Forward osmosis (FO) is a competitive alternative of thermal process for food liquid concentration. In this work, highly concentrated pear juice (TSS >60 °Bx, concentration factor ∼ 6.5-fold) was successfully produced by a single-run FO process using sodium lactate (NaLA) as the draw solute, and the properties of concentrates were compared with those produced by vacuum evaporation. The evolution of water flux, process resistance as well as the key physicochemical properties of pear juice over time during FO were assessed. The rheological properties of pear juice concentrates and salt accumulation during concentration were also analyzed. The results suggest that NaLA is a powerful draw solute as it can not only provide sufficient driving force to concentrate the pear juice from TSS 9.6 °Bx to 62 °Bx by a single-run treatment without any recharge of draw solute, but also deliver pear juice concentrates of better quality with higher antioxidant capacity, non-browning delightful color and richer aroma and flavor compared to those produced by vacuum evaporation. This work offers a reference of both theoretical and practical aspects for liquid food processing in the future. Highlights: Sodium lactate could be a promising draw solute for juice concentration. Pear juice could be concentrated to 62 °Bx (6.5-fold) by a single-run FO process. Overall concentrate quality of FO is much better than vacuum evaporation.